Narratives of resilience in 'coming out': the initial experiences of young South African persons who identify as gay and male - Viljoen, Judd Wilfred George (Rhodes University, Faculty of Humanities, Department of Psychology)
Access restricted. Expected release date in 2026
Keywords: Uncatalogued